Critical thickness of GaN film in controllable stress-induced self-separation for preparing native GaN substrates. (15th October 2019) - Li, Mengda; Cheng, Yutian; Yu, Tongjun; Wu, Jiejun; He, Jinmi; Liu, Nanliu; Han, Tong; Zhang, Guoyi
Abstract: Stress-induced self-separation is one of the most efficient process for preparing native GaN substrate. The control of GaN film thickness is the key point for GaN film separating from substrate completely. Considering the bowing of bilayer, we studied the radial stress in GaN film before separation. A shrunken circular delamination front model was proposed to derive the unrelaxed stress after separation, and the energy release rate for GaN/sapphire systems of different thicknesses was investigated during the whole separation process. A critical thickness about 500–700 μm was determined for separating 2-inch (5.08 cm) GaN film from a sapphire substrate. By precisely controlling the GaN film thickness around such critical thickness, the complete separation rate could be increased greatly to 74%, which is of great importance in realizing the industrialization of GaN substrate. Graphical abstract: Unlabelled Image Highlights: A controllable self-separation method was developed for preparing 2-inch GaN wafer. Critical thickness 500–700 μm was determined for complete separation of such wafer. Complete separation rate reached to 74% by controlling GaN at critical thickness.